Predictive value of hepatic ultrasound, liver biopsy, and duodenal tube test in the diagnosis of extrahepatic biliary atresia in Serbian infants - Boskovic, Aleksandra; Kitic, Ivana; Prokic, Dragan; Stankovic, Ivica; Grujic, Blagoje (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Extrahepatic biliary atresia (EHBA) is the most important cause of neonatal cholestasis. The validity of different diagnostic methods in the diagnosis of EHBA in developed countries has been presented elsewhere, but data from developing countries with low national incomes are scarce. The aim of this study was to investigate the relative accuracy and roles of abdominal ultrasonography, duodenal tube test (DTT), and liver biopsy in the diagnosis of EHBA in Serbia. Materials and Methods: The study included 156 infants with cholestasis admitted at the Mother and Child Health Care Institute. Data were collected according to the medical records observation technique. Results: Extrahepatic biliary atresia was diagnosed in 72 of 156 infants with cholestasis. The frequency was insignificantly higher in females than in males (1.25:1). Most patients were diagnosed prior to 60 days of life (median 58, range 30-67). In a group of 156 infants with cholestasis, 109 had ultrasound, liver biopsy, duodenal tube test, and intraoperative cholangiography done. Liver biopsy confirmed surgical disease in 71/109 patients and denied it in 38/109 patients (sensitivity- Sn 98%, specificity- Sp 100%, diagnostic efficiency of test- DgEf 99.08%). Duodenal tube test had Sn 97%, Sp 72%, and DgEf 88.99%, and the ultrasound findings showed Sn 78%, Sp 81%, and DgEf 77.92%. Five-year survival rate after Kasai operation was 76%. Conclusion: A well-coordinated multidisciplinary approach is required in the assessment of suspected cases of biliary atresia. Histology examination of biopsy specimens is an integral part of the diagnostic algorithm and, therefore, plays a pivotal role in the diagnostic evaluation of this disease.